Residue-based iron oxide catalyst for the degradation of simulated petrochemical wastewater via heterogeneous photo-Fenton process. Issue 20 (18th October 2018) - Scaratti, Gidiane; Rauen, Thalita Grando; Baldissarelli, Vanessa Zanon; José, Humberto Jorge; Moreira, Regina De Fátima Peralta Muniz
ABSTRACT: Iron oxide with a high degree of purity was recovered from waste and used as an environmentally friendly, low-cost catalyst in the application of the photo-Fenton process to simulated petrochemical wastewater (SPW). Iron oxide nanoparticles were characterized by X-ray powder diffraction, transmission electron microscopy, N2 adsorption/desorption isotherms, zeta potential, toxicity and atomic absorption spectrometry. The experiments were performed in a batch photochemical reactor, at 20 ± 2.0°C and pH 3.0. The SPW was efficiently mineralized and oxidized using a low catalyst dosage. The results showed that the organic compounds present in the wastewater were not adsorbed onto the solid surface. The solid was found to be stable with negligible leaching and low toxicity. The k TOC / k COD ratios were calculated and varied according to the process: for a homogeneous reaction, the ratio obtained was 0.31 and for the heterogenous photo-Fenton process, it was closer to 1. The chemical oxygen demand and total organic carbon removal values were very close, indicating that the SPW is immediately mineralized, without producing partially oxidized compounds. The residue-based goethite studied represents a good alternative to commercially available catalysts in terms of sources and availability.